2013
DOI: 10.1111/plb.12008
|View full text |Cite
|
Sign up to set email alerts
|

Observation of polyphosphate bodies and DNA during the cell division cycle of Synechococcus elongatus PCC 7942

Abstract: Although most cyanobacterial cells contain prominent polyphosphate bodies in the central cytoplasmic area enclosed by the peripheral thylakoid membranes, their roles are not fully understood. Storing phosphate for nucleotide production might be one of their important roles in survival of the cells. As a step towards identifying a possible contribution of the polyphosphate bodies to DNA synthesis, the relationship between polyphosphate bodies and DNA throughout cell division cycle of Synechococcus elongatus PCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 25 publications
0
30
1
Order By: Relevance
“…This can explain the dramatic decrease of polyP: cell, as cell growth entered exponential phase (Figs , after 7, 9 and 9 days respectively). Recurrent decrease in the polyP level immediately prior to and during nuclear division was commonly observed in other bacteria, suggesting that polyP may be utilized efficiently for nucleic synthesis (Rhee, ; Rao et al, ; Seki et al, ). The high rate of cell division in exponential growth, therefore, may have resulted in the decline of polyP: cell during the transition between the lag and exponential phases (Figs B, B and B), in contrast to polyP accumulation observed during the lag phase with the slow growth rate.…”
Section: Discussionmentioning
confidence: 95%
“…This can explain the dramatic decrease of polyP: cell, as cell growth entered exponential phase (Figs , after 7, 9 and 9 days respectively). Recurrent decrease in the polyP level immediately prior to and during nuclear division was commonly observed in other bacteria, suggesting that polyP may be utilized efficiently for nucleic synthesis (Rhee, ; Rao et al, ; Seki et al, ). The high rate of cell division in exponential growth, therefore, may have resulted in the decline of polyP: cell during the transition between the lag and exponential phases (Figs B, B and B), in contrast to polyP accumulation observed during the lag phase with the slow growth rate.…”
Section: Discussionmentioning
confidence: 95%
“…Increased concentrations of (p)ppGpp, the nucleotide second messengers of the stringent response, cause polyphosphate (polyP)-a linear polymer of orthophosphates-to accumulate in E. coli (12). We hypothesized that increased levels of (p)ppGpp might also be responsible for increased polyP levels recently observed in Synechococcus in the dark (13). Although previous work has shown that (p)ppGpp is synthesized by Synechococcus (8,14), mechanistic explanations for targets of the stringent response and its physiological effects are lacking, which led us to investigate the role of this pathway more broadly in Synechococcus.…”
Section: Resultsmentioning
confidence: 99%
“…This phosphate storage polymer might well be inorganic polyphosphate, because Synechocystis sp. PCC 6803 has been shown to synthesize polyphosphate (Morohoshi et al, 2002), like many other cyanobacteria (Grillo & Gibson, 1979;Lawrence et al, 1998;Gomez-Garcia et al, 2013;Seki et al, 2014;Zhang et al, 2015). The polyphosphate content during growth in the absence of phosphate was not analysed, because this was beyond the scope of this study.…”
Section: Growth and Ploidy Level In The Absence Of Phosphatementioning
confidence: 99%